(untitled) (Journal of Philosophy Culture and Political Science, 2018)
After Kazakhstan has received the UN non-permanent membership and became a chairman in two Security Council committees, the issue of resisting terrorism is both internal and external politics priority. Analyzing the date of the annual research Global Terrorism Index 2016: Measuring and Understanding the Impact of Terrorism, the authors demonstrate that terrorism is a complex phenomenon that cannot be reduced to the dominance of one single factor. At the same time, nowadays the religious, e.g. Islamic, component remains quite influential in activity of radical militant organizations. Therefore, the opposition to the “counterfeit Islam” should represent joint efforts of religious, academic and governmental institutions. The example of joined efforts of the University of Melbourne and “National Imams Consultative Forum” is given in the paper. The authors consider this experience as positive and suitable for Kazakhstan. Key words: Kazakhstan, Global Terrorism Index, the «counterfeit Islam», Salafis, global jihadism, imams training.